Observations préliminaires sur la reproduction des huîtres dans le bassin de Marennes-Oléron en 1971 - Gras, Paul; Comps, Michel; David, A.; Baron, G. (Bulletin Institut des Pêches Maritimes, 1971)
During the summer of 1970 mortality started in the Marennes-Oléron Basin which affected successively adult oysters, 18 year-old oysters and then the oyster spats collected the same year. Only the Portuguese oyster (Crassostrea angulata) was dying whereas the Pacific oyster (Crassostrea gigas) showed total resistance. The abnormal fixation of the 1970 spats, followed by an important mortality in this latter, and the large decrease of adult oyster stocks, and therefore of genitors, were also a reason for oyster farmers to worry as the new reproduction season was about to start. Some measures had to be taken in order to compensate for the lack of genitors susceptible of producing a tough and vivacious spat. The good results obtained for a few years with C. gigas and the almost certain reproduction opportunity with this species in the basin drove the leaders of the oyster culture sector to create, in a number of areas, some artificial Pacific oyster deposits. Several authors had studied the issues related to the exploitation and management of oyster deposits on French coasts (Ransson, 1951; Marteil, 1955; Le Dantec, 1955) and the knowledge acquired in this field had to be taken into account when introducing this new species, C. gigas. In this way, it has been agreed to concentrate a maximum of genitors in four parts of the basin considered as favourable for the extension of natural deposits; figure 1 precises their location. Au cours de l'été 1970 débuta dans le bassin de Marennes-Oléron une mortalité qui devait successivement affecter les huîtres adultes, les sujets de 18 mois puis le naissain capté l'année même. Seule l'huître portugaise (Crassostrea angulata) périssait alors que l'huître du Pacifique (Crassostrea gigas) montrait une résistance totale. La fixation anormalement faible du naissain en 1970, suivie d'une mortalité importante chez ce dernier, et la diminution très sensible du stock d'huîtres adultes, donc de géniteurs, représentaient autant de raisons d'inquiétude pour les ostréiculteurs à l'approche ...